Physical Characteristics, Total Phenolic, and Flavonoid Content of Coccinia grandis (L.) Voigt Leaves Extract - I Made Wisnu Adhi Putra; I Gusti Ayu Wita Kusumawati; Ni Luh Utari Sumadewi (Acta Chimica Asiana, 2021)
Coccinia grandis (L.) Voigt is an herbal plant that has been widely used for the treatment of various types of diseases. The phenolic and flavonoid content of plant extracts largely determine their pharmacological activity. The aim of this study was to determine the total phenolic and flavonoid contents of the ethanol extract of C. grandis leaves. Leaf samples in this study were obtained in the area of ​​Dalung, North Kuta, Badung, Bali. The powdered C. grandis leaf was extracted by maceration method using 70% ethanol followed by evaporation using an oven at 45oC to obtain a thick extract. The non-specific parameters of the extract were then determined, such as moisture content, ash content, and acid insoluble ash. Total phenolic content was determined using the follin-ciocalteu method and total flavonoid content was determined using the aluminum chloride method. Based on the research results, the yield of C. grandis leaf extract was 19.36%. C. grandis leaf extract has a description of a thick and sticky extract, blackish brown color, distinctive aroma, and a bitter sour taste. The water content of the ethanolic extract of C. grandis leaves was 9.93±0.03% (g/g). The total ash value of the simplicia and ethanolic extract of C. grandis leaves were 20.76±0.15% (g/g) and 27.38±0.19% (g/g), respectively. The acid insoluble ash content of the extract was 4.05±0.30% (g/g). The total phenolic and total flavonoid contents of the extract were 111.92±0.49 µg GAE/mg dry extract and 73.60±3.53 µg QE/mg dry extract, respectively.